Manajemen Rantai Pasok Pupuk Subsidi Solusi Untuk Mengatasi Tantangan Kelangkaan Di Sektor Pertanian Padi Di Kecamatan Maritengngae Kabupaten Sidenreng Rappang - Rahmadhana M Nasir; Muh Tamrin; Rahman Yakub; Sofyan B (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
The scarcity of subsidized fertilizer remains a significant challenge in the rice farming sector in Indonesia, including in Maritengngae District, Sidenreng Rappang Regency. This study aims to analyze the distribution conditions of subsidized fertilizer, identify obstacles in supply chain management, and formulate effective strategies to ensure its sustainable availability. A descriptive qualitative method was employed, with data collected through in-depth interviews, field observations, and documentation. Informants consisted of farmers, fertilizer distributors, agricultural extension officers, and officials from the Department of Agriculture. The collected data were analyzed thematically and supported by NVivo 12 Pro software to identify the frequency of emerging themes and the relationships between key factors contributing to fertilizer shortages. The findings reveal that although the local availability of fertilizer has relatively improved, major issues such as delayed deliveries, weak coordination between farmer groups and distributors, and climate-related challenges continue to affect the effectiveness of distribution. Recommended strategies include strengthening stakeholder collaboration, optimizing digital information systems, and adjusting distribution policies to be more responsive to local needs.